Trypanosoma brucei histones are heavily modified with combinatorial post-translational modifications and mark Pol II transcription start regions with hyperacetylated H2A. Issue 17 (12th September 2022) - Maree, Johannes P; Tvardovskiy, Andrey; Ravnsborg, Tina; Jensen, Ole N; Rudenko, Gloria; Patterton, Hugh-G
Abstract: Trypanosomes diverged from the main eukaryotic lineage about 600 million years ago, and display some unusual genomic and epigenetic properties that provide valuable insight into the early processes employed by eukaryotic ancestors to regulate chromatin-mediated functions. We analysed Trypanosoma brucei core histones by high mass accuracy middle-down mass spectrometry to map core histone post-translational modifications (PTMs) and elucidate cis -histone combinatorial PTMs (cPTMs). T. brucei histones are heavily modified and display intricate cPTMs patterns, with numerous hypermodified cPTMs that could contribute to the formation of non-repressive euchromatic states. The Trypanosoma brucei H2A C-terminal tail is hyperacetylated, containing up to five acetylated lysine residues. MNase-ChIP-seq revealed a striking enrichment of hyperacetylated H2A at Pol II transcription start regions, and showed that H2A histones that are hyperacetylated in different combinations localised to different genomic regions, suggesting distinct epigenetic functions. Our genomics and proteomics data provide insight into the complex epigenetic mechanisms used by this parasite to regulate a genome that lacks the transcriptional control mechanisms found in later-branched eukaryotes. The findings further demonstrate the complexity of epigenetic mechanisms that were probably shared with the last eukaryotic common ancestor.